Flashcards as a Tool for Vocabulary Enhancement: A Study on Tenth Grade Students at SMA Negeri 1 Padang Bolak Julu - Ritonga, Sinta Nuria; Sari, Siti Meutia; Harahap, Tinur Rahmawati; Mahrani (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2024)
This study aims to investigate the effect of using flashcards in vocabulary teaching on improving students' vocabulary acquisition at SMA Negeri 1 Padang Bolak Julu. The method used was classroom action research which consisted of two cycles. The data collection instruments were pre-test, post-test cycle 1 and post-test cycle 2 along with observation and interview. The data were statistically analyzed by calculating the mean and percentage increase in students' scores. The results showed that the use of flashcards was effective in improving students' vocabulary mastery. The average score of the students increased from 43.67 in the pre-test to 82.5 in the second cycle post-test. The percentage of score increase from the pre-test to the second cycle post-test was 88.9%. In addition, 83.33% of the students successfully achieved the minimum criteria (KKM) at the end of the second cycle. The results of this study support the hypothesis that the use of flashcards has a significant positive impact on vocabulary learning.